MEKTEPKE SHEKEMGI JASTAǴÍ BALALARDÍŃ SÓYLEW TILIN RAWAJLANDÍRÍWDA NAQÍL-MAQALLARDÍŃ ÁHMIYETI - Shamuratova, X. (ILIM hám JÁMIYET, 2023)
The article defines the meaning and place of Karakalpak folk proverbs and sayings in the development of the speech of preschool children, in the education and formation of their moral and aesthetic qualities.